PECULIARITIES OF POLICE CORPS OFFICERS’ PROFESSIONAL TRAINING AT THE POLICE CORPS ACADEMY OF THE SLOVAK REPUBLIC (Comparative Professional Pedagogy, 2022)
The article is devoted to the disclosure of the peculiarities of the professional training of Police Corps officers of the Slovak Republic, and the professional education at the Academy of the Police Corps of the Ministry of Internal Affairs of Slovakia in particular. The content of the professional training of future Police Corps officers of the Slovak Republic in the departmental educational institution has been analyzed. It has been established that at the Academy, cadets of higher education undergo training at three levels of education (Bachelor, Master and Doctorate) in accordance with generally accepted European standards of professional training of border guards and the adopted Unified Basic Level Curriculum for the training of border guard specialists (Common Core Curriculum) developed by the FRONTEX agency (European Border and Coast Guard Agency). It has been defined that Police Corps officers obtain higher education at three levels of education. Thus, the Bachelor's degree lasts for 3 years full-time and 4 years part-time. Police officers also obtain the Master’s degree in both forms of education. The term of study is 2 years (full-time) and 3 years - part-time, respectively. In addition, Masters’ students take an oral exam to obtain a Doctor of Philosophy. Doctoral students study 3 years (full-time) and 4 years (part-time), respectively. The education received by the graduates of the above-mentioned departmental educational institution is equivalent to that which prepares the personnel of other police agencies of the EU countries. This ensures the mobility of graduates not only within Slovakia, but also within the European Union.A detailed analysis of the accredited training curricula “Law Enforcement Insurance of the Security of People and Facilities” and “Law Enforcement Services in Public Administration” has been carried out. It has been determined that the training at the Police Corps Academy in Bratislava is conducted in accordance with them.The structure of the above-mentioned professional training has been characterized, namely forms of education (full-time and part-time), training terms and educational workload (list of academic disciplines, their distribution by semesters and types of classes, etc.).
Keywords: professional training; educational curricula; training of Police Corps officers; Academy of the Police Corps in the city of Bratislava; the Slovak Republic